Interface-engineered CuBi2O4/biomass-derived activated carbon composites for supercapacitors - J. Venkatesan; J. Preethi Rency Fathima; J. Bosco Franklin; A. Padmanaban; A. Kumaresan; S. John Sundaram; P. Maadeswaran; Kasinathan Kaviyarasu (Biomass and Bioenergy, 2026)

Floral Phenology and Changes in Economic Traits During Different Stages of Fruit Growth and Development in Seven Avocado Accessions - Vittal Kamble; Narayana C.K.; Sudhakar Rao D.V.; Karunakaran G.; Sangeetha Priya S.; Vijay Rakesh Reddy S.; Preethi P. (Applied Fruit Science, 2026)

Computational screening of lichen bioactive compounds as a potential antiviral agent against SARS-CoV-2 main proteases - S. Jeya Preethi; A. Yamuna; M. Arunkumar; E. Murugesh; P. Ponmurugan; P. Shanmughavel (In Silico Pharmacology, 2026)

Synergistic Effects of Ethylene Inhibitors and Cold Storage on the Postharvest Quality of Papaya Fruits - Pavankumar M; Sudhakar Rao D. V.; Vijay Rakesh Reddy Sanikommu; Preethi P.; Vasugi C.; Shivasankara K. S.; Sriram S. (Applied Fruit Science, 2026)

Prolonging sapota fruit quality and storage life through essential oil-mediated antioxidant and defence enzyme regulation system - N.B. Brunda; D.V. Sudhakar Rao; S.Vijay Rakesh Reddy; P. Preethi; J. Satisha; K.S. Shivashankara (Journal of Stored Products Research, 2026)

Health risks due to geogenic and anthropogenic influences on groundwater quality in Southern India's hard rock terrain - B. Preethi; T. Subramani; R. Saravanan; P. Gopinathan; Zaixing Huang; Brajesh Kumar (Journal of Geochemical Exploration, 2025)

Exploring Withanolides from Withania somnifera: A Promising Avenue for Alzheimer’s Disease Treatment - Chitikela P Pullaiah; Preethi Priyadharshini SP; Phareedha SK; Yamini Nemalapalli; Geetha Birudala; S Lahari; Shanmugam Vippamakula; R Shakila; Muni Swamy Ganjayi; Raghavendra Mitta (Current Pharmacology Reports, 2025)

A comprehensive review on human health hazards due to groundwater contamination: A global perspective - Meera Rajan; D. Karunanidhi; J. Jaya; B. Preethi; T. Subramani; P. Aravinthasamy (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Exploring the Potential of Nickel Oxide Nanoparticles Synthesized from Dictyota bartayresiana and its Biological Applications - G. V. Geethamala; A. V. Swathilakshmi; S. Keerthana; D. Vidhyanivetha; G. Preethi; P. Chitra; M. Poonkothai (Biological Trace Element Research, 2024)

Computing the Quality Characters and Acceptability of Convective Air Dried Germinated Cashew Seed Powders - P. Preethi; S. Mangalassery; S. V. R. Reddy; T. Harish; G. L. Veena; R. Pandiselvam (Applied Fruit Science, 2024)

Plant based surfactant combined sonication pretreatment on food waste for biomethane generation: Cost and energy procurement - K. Ajay Krishna Dev; Preethi; P. Rajaguru; M. Gunasekaran; J. Rajesh Banu (Fuel, 2024)

Differential Efficacy of Postharvest Application of Ethylene Inhibitors on Storage Life and Nutritional Quality of Guava (cv. ‘Arka Mridula’) - A. J. Sachin; D. V. Sudhakar Rao; K. Ranjitha; C. Vasugi; C. K. Narayana; S. Vijay Rakesh Reddy; P. Preethi (Applied Fruit Science, 2024)

Bioprospecting of novel peroxidase from Streptomyces coelicolor strain SPR7 for carcinogenic azo dyes decolorization - P. Sai Preethi; Sundaram Vickram; Raja Das; N.M. Hariharan; M. Rameshpathy; R. Subbaiya; N. Karmegam; Woong Kim; M. Govarthanan (Chemosphere, 2023)

Mixed polyaromatic hydrocarbon degradation by halotolerant bacterial strains from marine environment and its metabolic pathway - Manasa Muralidharan; K. Veena Gayathri; P. Senthil Kumar; D.S. Preethi; R. Kavitha; Revathy Rajagopal; Gayathri Rangasamy (Environmental Research, 2023)

Changes in Growth and Developmental Stages of Nuts of Selected Cashew (Anacardium occidentale) Varieties in West Coast Region of Karnataka - Babli Mog; J. D. Adiga; P. Preethi; M. G. Nayak (Agricultural Research, 2022)

Spatial assessment of Groundwater Quantity and Quality: A case study in parts of Chidambaram Taluk, Cuddalore District, Tamil Nadu, India - S. Venkatesan; S. Arumugam; M. Bagyaraj; T. Preethi; P. Parthasarathy (Sustainable Water Resources Management, 2021)

Role of physical oceanography parameters in ocean’s biological response with the passage of cyclone Titli in the Bay of Bengal - K Vijay Prakash; Ch S Geetha Vimala; P V Nagamani; N K Baranval; Shivashankar Manche; T Preethi Latha; I V G Bhavani; Y Umamaheswara Rao; Ch S N Phanindra; K Srinivas; K P Kumari (Journal of Earth System Science, 2021)

Assessment of Water Quality Along the Southeast Coast of India During COVID-19 Lockdown - K. Vijay Prakash; Ch. S. Geetha Vimala; T. Preethi Latha; Chiranjivi Jayaram; P. V. Nagamani; Ch. N. V. Laxmi (Frontiers in Marine Science, 2021)
The COVID-19 pandemic has affected the entire world and has had a devastating impact on both lives and livelihoods in India. The only way to defeat the rapid spread of COVID-19, is to shut down socio-economic activities and to maintain minimal human interaction with the implementation of a lockdown. Such lockdowns have manifested in a pollution curtailment in almost all spheres of the planet, including in marine pollution. Quantifying this decrease in pollution levels enables the scientific community to assess the contribution of anthropogenic (especially non-essential) activities to global/regional pollution levels. This paper aims to study the impact of the stringent lockdown period (phase 1 and 2) on coastal water quality along the Chennai coast of India, by analyzing suspended matter concentration (SPM), a key element of water quality and diffuse attenuation coefficient, K d (490), using LANDSAT-8 Operational Land Imager (OLI) data. LANDSAT-8/OLI, L1TP scenes were subjected to radiometric calibration and atmospheric correction to derive surface reflectance values from raw digital numbers using ACOLITE software and a brief insight has been given for the Dark Spectrum Fitting algorithm used in ACOLITE. SPM concentration decreased by 15.48 and 37.50% in the Chennai and Ennore ports, respectively, due to minimal vessel movement and cargo handling. The stringent lockdown led to the operation of fewer thermal plant units, thus less fly ash was emanated, resulting in a 28.05% reduction in SPM levels over Ennore creek. As industrial and commercial activities subsided, the city’s water bodies became clearer than they were just a fortnight prior to the lockdown, with a reduction of 22.26% of SPM in Adyar and 33.97% in Cooum riverine estuaries. Decrease in K d (490) showed a positive relationship with SPM and thus improved coastal water quality because of the reduction of SPM during this period. The variations in PM2.5 and PM10 concentrations were studied using National Air Quality Monitoring Programme (NAMP) data and reduced levels in particulate matter concentration (PM2.5 and PM10) for the Adyar residential area (24.38 and 28.43%) and for the Nungampakkam commercial area (36.09 and 67.18%) were observed. A significant reduction in PM2.5 concentration (45.63%) was observed in the Ennore-Manali Industrial region.

Development of EST-SSR markers for genetic diversity analysis in coconut (Cocos nucifera L.) - P. Preethi; Shafeeq Rahman; S. Naganeeswaran; A. A. Sabana; K. P. Gangaraj; B. A. Jerard; V. Niral; M. K. Rajesh (Molecular Biology Reports, 2020)

Thermodynamics of ferredoxin binding to cyanobacterial nitrate reductase - Anurag P. Srivastava; Neelam Mishra; Ramachandra L. A. Prasad; Preethi Rajesh; David B. Knaff (Photosynthesis Research, 2020)

Neurophysiological and Neuropsychological Analysis of the Cognitive Functions in Dysthyroid Female Patients - P. Mishra; B. L. Preethi; P. Kalra (Neurophysiology, 2018)

Comprehensive strategy for the design of precision drugs and identification of genetic signature behind proneness of the disease—a pharmacogenomic approach - Preethi M Iyer; S Karthikeyan; P Sanjay Kumar; P K Krishnan Namboori (Functional & Integrative Genomics, 2017)

Satellite and In Situ Observations of a Phytoplankton Bloom from Coastal Bay of Bengal: Role in pCO2 Modulation - Rajdeep Roy; K. H. Rao; T. Preethi Latha; Vinay Kumar Dadhwal; V. V. S. S. Sarma; P. V. Nagamani; S. B. Choudhury; Seetharam Pondala (Journal of the Indian Society of Remote Sensing, 2017)

Anomalous convective activity over sub-tropical east Pacific during 2015 and associated boreal summer monsoon teleconnections - Milind Mujumdar; K. P. Sooraj; R. Krishnan; B. Preethi; Manish K. Joshi; Hamza Varikoden; Bhupendra B. Singh; M. Rajeevan (Climate Dynamics, 2017)

Estimation of Air-Sea CO2 Flux in the Coastal Waters of Visakhapatnam - T. Preethi Latha; K. H. Rao; V. V. S. S. Sarma; P. Seetaram; S. B. Choudhury; P. V. Nagamani; C. B. S. Dutt; V. K. Dhadwal; Sudip Manna (Journal of the Indian Society of Remote Sensing, 2015)

Setting of Cloud Albedo in the Atmospheric Correction Procedure to Generate the Ocean Colour Data Products from OCM-2 - P. V. Nagamani; T. Preethi Latha; K. H. Rao; T. Suresh; S. B. Choudhury; C. B. S. Dutt; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2015)

Retrieval and Validation of Chlorophyll-a Concentrations in the Coastal Waters Off Yanam and Kakinada (Godavari) Basin Along East Coast of India - T. Preethi Latha; P. V. Nagamani; K. H. Rao; S. K. Dash; S. B. Choudhury; Aziz Rehman; V. V. S. S. Sarma; M. Naveen Babu; P. Amarendra; B. Srinivasa Rao; T. D. V. Prasad (Journal of the Indian Society of Remote Sensing, 2014)

Synthesis of antihyperglycemic, α-glucosidase inhibitory, and DPPH free radical scavenging furanochalcones - R. Ranga Rao; Ashok K. Tiwari; P. Prabhakar Reddy; K. Suresh Babu; G. Suresh; A. Zehra Ali; K. Madhusudana; Sachin B. Agawane; Preethi Badrinarayan; G. Narahari Sastry; J. Madhusudana Rao (Medicinal Chemistry Research, 2012)

Evaluation of Flow Rate, pH, Buffering Capacity, Calcium, Total Proteins and Total Antioxidant Capacity Levels of Saliva in Caries Free and Caries Active Children: An In Vivo Study - B. P. Preethi; Dodawad Reshma; Pyati Anand (Indian Journal of Clinical Biochemistry, 2010)